Strategies for increased fodder production from Leucaena and Gliricidia to eliminate dry season feed shortages in the humid tropics - Cobbina, J. (Informa UK Limited, 1995)
Fodder tree legumes are valuable sources of high quality feed in the dry season when pasture productivity can be low and of poor quality. To ensure sustained fodder availability from Leucaena leucocephala (Lam.) de Wit and Gliricidia sepium (Jacq.) Walp in the dry season (November-February) the best strategy is to allow hedges to grow for 9 months through the rainy season after a uniform pruning in January, then cut and sun-dry. The copice growth should then be cut again 3 months later in January and fed as green-chop.